Environmental factors affecting the development of the Zoophycos ichnofacies in the Lower Cretaceous Río Mayer Formation (Austral Basin, Patagonia) - Richiano, Sebastián Miguel (2015)
The Río Mayer Formation (Berriasian-Albian) is part of the basal infill of the Austral Basin, southwestern Gondwana. In the Los Glaciares National Park (Santa Cruz Province) seven sections were sedimentologically studied in detail. The investigated interval is mainly composed of black mudstones and shales interbedded with marls and fine-grained sandstones. The vertical distribution of these lithologies provided the basis to distinguish three major units (lower, middle and upper). In general, within the Río Mayer Formation, two different developments of the Zoophycos ichnofacies were recognized. First, in the middle unit (Valanginian-Hauterivian), this ichnofacies shows a high degree of bioturbation having a bioturbation index (BI) between 3 and 4; Zoophycos specimens are of large size, the spreiten are nearly 1. cm in height and more than 1. m in width. This ichnogenus is associated with Chondrites and Bergaueria perata. Environmentally this ichnofacies formed during a transgression, the sedimentation rates were very low and promoted the accumulation of benthic food in the outer shelf. Second, the Zoophycos ichnofacies in the upper unit (Albian) exhibits a less intense degree of bioturbation (BI between 0 and 1) and; Zoophycos is of relatively small size, the spreiten are 0.3. cm high and short. Typically are associated Ophiomorpha, Chondrites, Palaeophycus and Teredolites. When this ichnofacies formed, the prodelta margin prograded across the outer shelf and led to enhanced sedimentation rates further offshore resulting in the dilution of the nutrients.